2012
DOI: 10.1002/bies.201200013
|View full text |Cite
|
Sign up to set email alerts
|

NAIPs: Building an innate immune barrier against bacterial pathogens

Abstract: The innate immune system of mammals encodes several families of immune detector proteins that monitor the cytosol for signs of pathogen invasion. One important but poorly understood family of cytosolic immunosurveillance proteins is the NLR (nucleotide-binding domain, leucine-rich repeat containing) proteins. Recent work has demonstrated that one subfamily of NLRs, the NAIPs (NLR family, apoptosis inhibitory proteins), are activated by specific interaction with bacterial ligands, such as flagellin. NAIP activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 96 publications
1
19
0
Order By: Relevance
“…Although the finding appears paradoxical in view of the important role of MyD88 for innate immune functions, it is possible that its absence affects the cytosolic response such that the cytosol will not be permissive for LVS and Listeria, e.g., by the lack of essential metabolites. Recent studies have identified that the release of bacterial components, e.g., DNA, from the phagosome induces a specific cytosolic response (11,12,51,71,72). Although it is often assumed that the sensing of bacterial products is a prerequisite for the control of intracellularly located bacteria, it is possible that successful intracellular pathogens have developed means to exploit this host response to their advantage and that, in fact, it is a necessity for the intracytosolic bacterial replication in certain cell types.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the finding appears paradoxical in view of the important role of MyD88 for innate immune functions, it is possible that its absence affects the cytosolic response such that the cytosol will not be permissive for LVS and Listeria, e.g., by the lack of essential metabolites. Recent studies have identified that the release of bacterial components, e.g., DNA, from the phagosome induces a specific cytosolic response (11,12,51,71,72). Although it is often assumed that the sensing of bacterial products is a prerequisite for the control of intracellularly located bacteria, it is possible that successful intracellular pathogens have developed means to exploit this host response to their advantage and that, in fact, it is a necessity for the intracytosolic bacterial replication in certain cell types.…”
Section: Discussionmentioning
confidence: 99%
“…To combat the latter group, the macrophage utilizes cytosolic sensors belonging to the Nod-like receptor (NLR) or AIM2-like receptor families (11,12). Engagement of these receptors leads to the formation of the inflammasome, a multiprotein complex composed of a sensor protein belonging to the NLR or AIM2-like families, an adaptor protein, ASC, and caspase-1 (13).…”
mentioning
confidence: 99%
“…Extracellular flagellin is recognized by TLR5 (16) but it can be delivered to the cell cytosol though the secretion systems present in virulent bacteria strains, such as the S. typhimurium type III secretion system (T3SS SPI-1) and L. pneumophila type IV (T4SS). In the cell cytosol, flagellin induces the formation of the NAIP5/NLRC4 inflammasome, leading to the subsequent activation of caspase-1 (17, 18, 23). Notably, the activation NAIP5/NLRC4 inflammasomes by cytosolic flagellin occurs independently of TLR5 (20), and these two receptors recognize distinct regions of flagellin (16).…”
Section: Assembly and Activation Of Naip/nlrc4 Inflammasomesmentioning
confidence: 99%
“…Notably, the activation NAIP5/NLRC4 inflammasomes by cytosolic flagellin occurs independently of TLR5 (20), and these two receptors recognize distinct regions of flagellin (16). TLR5 senses a region present in the D1 domain of the protein, whereas the amino acid sequences recognized by NAIP5/NLRC4 inflammasomes are in the D0 domain of the molecule (18, 23, 19, 21, 22). …”
Section: Assembly and Activation Of Naip/nlrc4 Inflammasomesmentioning
confidence: 99%
“…Also, NAIPs lack certain caspase-interaction residues within the BIR domains that would be necessary for direct inhibition of caspases, raising concern about whether NAIP can inhibit caspases in physiological settings (Scott et al, 2005;. Additionally, NAIPs mediate inflammasome-induced caspase-1 activation and induction of pyroptosis via NLRC4, which is contrary to the suggested inhibitor of apoptosis function (Kofoed and Vance, 2012). BIR domains, however, can mediate a broad range of protein-protein interactions and therefore could be implicated in diverse cellular functions in addition to inhibition of caspases.…”
mentioning
confidence: 99%